(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
The gamification of education can enhance levels of students’ engagement similar to what games can do, to improve their particular skills and optimize their learning. This article goes into details about enjoyable experience of gamification in teaching, its main goals and benefits for learners. It aims to assess whether the use of gamification is likely to facilitate or undermine intrinsic motivation, and presents a summary of self-determination theory